Telecommunications in the European internal market - Jürgen Müller (Intereconomics, 1989)
The completion of the European internal market by 1992 is one of the EC Commission's key objectives. European integration is to be given fresh impetus by removing remaining frontier controls and trade barriers, liberalising public procurement and limiting the number of sectors protected from competition, such as finance, transport and communications. The following article analyses the possible effects of the proposals concerning telecommunications equipment and services outlined in a Green Paper from the Commission.
Keywords: 330; European Community